Integrated approaches to understanding animal exploitation and dairying in the Central European Early Neolithic: a case study from Ludwinowo 7 (Kuyavia, Poland; c. 5250–5000 cal BC) - Smyth, Jessica; Gillis, Rosalind E.; Roffet-Salque, Mélanie; Johnson, Emily V.; Kendall, Iain P.; Krueger, Marta; Pyzel, Joanna; Heyd, Volker; Marciniak, Arkadiusz; Vigne, Jean-Denis; Balasse, Marie; Outram, Alan K.; et al. (Frontiers in Environmental Archaeology, 2023)
Recent genetic studies point towards 6th millennium BC central Europe as the core region for the emergence of the lactase persistence (LP) gene mutation -13,910*T, making it important to understand the intensity of milk production and consumption among Linearbandkeramik (or LBK) farming groups. However, it is not known if milking was part of the LBK Neolithic “package” from the start, or if it displayed a discontinuous pattern in time and space. Documenting the changing nature of prehistoric animal exploitation requires integrating multiple strands of evidence and here we detail multi-proxy research into animal management strategies and the intensification of dairying in Neolithic Europe, using the LBK site of Ludwinowo 7 in central Poland as a case study. Lipid biomarker and stable isotope compositions of food residues from vessels provide qualitative and quantitative assessments of the major animal products acquired and processed, while zooarchaeological analyses identify slaughter and butchery practices, revealing the nature of meat, milk and fat exploitation. Stable carbon and oxygen isotope analyses on cattle teeth are also undertaken to define seasonal herd management. This combined approach offers an integrated picture of animal exploitation and milk use at the central European LBK site of Ludwinowo.